Simulation and Design of Lead Acid Pspice Battery Model with Bidirectional Converter - Kubba, Zainab M; Al-Azzawi, Zeena Mowafaq (Al-Nahrain Journal of Science, 2018)
This search discusses the simulated and design of the battery model. The simulated is carried out using Personal Simulation Program for Integrated Circuits Emphasis PSPICE software for the complete model in order to get the results for the proposed battery model. The PSPICE lead acid battery model is consists of the charge efficiency and Battery voltage components. Details are also given to the method of measuring the charge efficiency then the battery model will be tested as input source to the bidirectional Buck-Boost converter to verify its validity.